SUCCESOR OF HOMER: DAFINA FROM THE VILLAGE OF PROSENIK, SERRES AREA - Koviloski, Slavcho (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
In this paper we refer to the life of one of the most famous Macedonian interpreters of folk songs from the XIX century, Dafina from the village of Prosenik, Serres area. She was the most significant informant of Stefan Verkovich, who had written a number of songs from her, of which 275 have been determined so far. Because of the skill and beauty of the songs, Verkovich called her “Homer’s successor” and "a woman with rare wit and unusual gift to remember". Her poems are with different themes and motifs, rich in metaphors, epithets, a rich fund of personal names and toponyms, etc. Therefore, Dafina’s songs represent a small remembrance to the rich cultural and historical past of the Macedonians.